Plant stress and the prevalence of pests and pathogens associated with a native and an invasive alien legume tree in the Cape Floristic Region, South Africa - Van der Colff, Dewidine (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.